Aviation, transport services : agreement between the United States of America and Iceland, signed at Washington June 14, 1995 with annexes. - Iceland.; United States. Treaties, etc. Iceland, 1995 June 14.; United States. Department of State. (Washington, D.C. : Dept. of State : For sale by the Supt. of Docs., U.S. G.P.O., 2000)
Mode of access: Internet.